Effect of lutein extract from spinach (Amaranthus sp) on n-hexane fraction on bulk cooking oil peroxide numbers - Aryanie, Novia; Kurniasih, Nunung; Rosahdi, Tina Dewi; Junitasari, Assyifa (Asian Journal of Health and Applied Sciences, 2022)
The use of cooking oil for too long can cause rancidity in cooking oil which produces cancer-triggering free radicals. This rancidity can be overcome by adding antioxidants, namely compounds that can ward off free radicals. Lutein is an antioxidant compound that contains a hydroxyl group. In this study, green spinach leaves were used as a source of lutein. Green spinach leaves have a high lutein content that is not inferior to Kenikir and Broccoli flowers. The purpose of this study was to analyze the effect of adding lutein as an antioxidant compound in bulk cooking oil. The test begins with the maceration extraction stage using n-hexane solvent, determining the Rf value of lutein with TLC using an eluent mixture of n-hexane: acetone: chloroform (6: 2: 2) and analyzed by iodometric titration method. The results show that lutein has an Rf value of 0.58, which is almost the same as the standard Rf of lutein, which is 0.59, while the lutein content in green spinach leaves is quite high at 7.86 ppm. Lutein can inhibit the rancidity process caused by an increase in the number of peroxides. At a concentration of 3% lutein has a peroxide value smaller than 1% tocopherol which in this study was used as a comparison, namely synthetic antioxidant compounds.